You have the the length of segment NK is 23.
Furthermore, you have that segment NK is the sum of the following segments:
NK = NM + ML + LK
Each of the previous segments are given by the following algebraic expressions:
NM = x - 6
ML = 9
LK = 2x - 19
You sum the previous expression, by taking into account that the result is 23. Then you solve for x, just as follow:
NM + ML + LK = NK
(x - 6) + (9) + (2x - 19) = 23 eliminate parenthesis
x - 6 + 9 + 2x - 19 = 23 simplify similar terms
x + 2x - 6 - 19 + 9 = 23
3x - 16 = 23 add 16 both sides
3x = 23 + 16
3x = 39 divide by 3 both sides
x = 39/3
x = 13
Hence, the solution for x is x = 13